Land supply marketization, economic fluctuations and welfare: A quantitative analysis for China - He, Yiyao; Wu, Mengyuan; Jiang, Haiwei (International Journal of Strategic Property Management, 2024)
Land supply in China is planned by governments, and the supply ratios of various types of land are in relatively rigid administrative control. This paper constructs a DSGE model to study the relationship between land supply marketization in China and economic fluctuations. Moreover, this paper evaluates the social welfare gains from land marketization. We document that the government’s land planning constraint impacts consumption and social welfare through the land price and final output, causing resource misallocation losses in aggregate investment and output. Quantitatively, the optimal upper limit of industrial land supply is about 40% to achieve the maximum social welfare. This paper stresses the necessity of revitalizing China’s land market, and simultaneously speeding up the marketization of collectively operated construction land.